Combined analysis of mRNA–miRNA from testis tissue in Tibetan sheep with different FecB genotypes - Sun Wu; Ma Shike; Jin Xiayang; Ma Yuhong (Open Life Sciences, 2023)
Testis size is important for identifying breeding animals with adequate sperm production. The aim of this study was to survey the expression profile of mRNA and miRNA in testis tissue from rams carrying different FecB genotypes, including the wild-type and heterozygous genotypes in Tibetan sheep. Comparative transcriptome profiles for ovine testes were established for wild-type and heterozygote Tibetan sheep by next-generation sequencing. RNA-seq results identified 3,910 (2,034 up- and 1,876 downregulated) differentially expressed (DE) genes and 243 (158 up- and 85 downregulated) DE microRNAs (miRNAs) in wild-type vs heterozygote sheep, respectively. Combined analysis of mRNA-seq and miRNA-seq revealed that 20 miRNAs interacted with 48 true DE target genes in wild-type testes compared to heterozygous genotype testes. These results provide evidence for a functional series of genes operating in Tibetan sheep testis. In addition, quantitative real-time PCR analysis showed that the expression trends of randomly selected DE genes in testis tissues from different genotypes were consistent with high-throughput sequencing results.